Bioethical didactic methodology. Proposals and considerations on the document of the National Committee of Bioethics - Mele, Vincenza; Palazzani, Laura (Medicina e Morale, 1992)
After a brief synthesis of the document of the National Committee of Bioethics on "Bioethics and health care system education", the article expresses some considerations. The authors underline the importance of the subject regarding the new ethical issues arising from the rapid progress in science and technology, as well as the difficulty in proposing a uniformity within the context of the moral pluralism in contemporary society. The second part focuses on teaching methodology in bioethics and refers to philosophical-theoretical considerations (the connection between methodology and contents) together with pedagogical considerations (the connection between methodology and the characteristics of the students).